Central Dopamine D2 Receptors Regulate Growth-HormoneDependent Body Growth and Pheromone Signaling to Conspecific Males - Noain, Daniela Maria Clara (2013)
Competition between adult males for limited resources such as food and receptive females is shaped by the male pattern of pituitary growth hormone (GH) secretion that determines body size and the production of urinary pheromones involved in male-to-male aggression. In the brain, dopamine (DA) provides incentive salience to stimuli that predict the availability of food and sexual partners. Although the importance of the GH axis and central DA neurotransmission in social dominance and fitness is clearly appreciated, the two systems have always been studied unconnectedly. Here we conducted a cell-specific genetic dissection study in conditional mutant mice that selectively lack DA D2 receptors (D2R) from pituitary lactotropes (lacDrd2KO) or neurons (neuroDrd2KO). Whereas lacDrd2KO mice developed a normal GH axis, neuroDrd2KO mice displayed fewer somatotropes; reduced hypothalamic Ghrh expression, pituitary GH content, and serum IGF-I levels; and exhibited reduced body size and weight. As a consequence of a GH axis deficit, neuroDrd2KO adult males excreted low levels of major urinary proteins and their urine failed to promote aggression and territorial behavior in control male challengers, in contrast to the urine taken from control adult males. These findings reveal that central D2Rs mediate a euroendocrineexocrine cascade that controls the maturation of the GH axis and downstream signals that are critical for fitness, social dominance, and competition between adult males.